Erythrocytosis secondary to autonomous non-tumoural production of erythropoietin - Ducla-Soares, J. L. (2000)
The case of a 24-year-old man, erythrocyanoticsince birth, with secondary erythrocyanosis, isdescribed. Investigation identified autonomous (non-tumoural) production of erythropoietin which wasunresponsive to isovolemic phlebotomies.